11C-PiB PET studies in typical sporadic Creutzfeldt–Jakob disease. Issue 9 (29th March 2009) - Villemagne, V L; McLean, C A; Reardon, K; Boyd, A; Lewis, V; Klug, G; Jones, G; Baxendale, D; Masters, C L; Rowe, C C; Collins, S J
Abstract : Objective: Brain amyloid imaging using positron emission tomography (PET) is of increasing importance in the premortem evaluation of dementias, particularly in relation to Alzheimer disease (AD). The purpose of this study was to explore the premortem diagnostic utility of 11 C-PiB PET in sporadic Creutzfeldt–Jakob disease (CJD). Methods: Two patients, 72 and 59 years old, underwent evaluation for rapidly progressive cognitive decline, dying after illness durations of 5 and 7 months, respectively. As part of their comprehensive assessment, 18 F-FDG PET and 11 C-PiB PET studies were performed approximately 2–4 weeks prior to death, and the brain regional distributions compared with those from cohorts of healthy controls (HC) and AD patients. Results: Routine investigations, including brain MRI scans, revealed changes typical of sporadic CJD, with the diagnosis confirmed at autopsy in both patients. The 18 F-FDG PET showed global hypometabolism in one patient and thalamic and frontal hypometabolism with unexpected hypermetabolism in the dentate nuclei of the cerebellum in the other. Neither patient displayed cerebral cortical 11 C-PiB PET retention above the levels observed in HC. Conclusions: No grey-matter 11 C-PiB retention was observed in two pathologically confirmed cases of typical sporadic CJD. We speculate that low PrP plaque density and small plaque size, as well as a relatively low affinity of the radioligand, explain the absence of 11 C-PiB retention. More studies to validate this hypothesis are warranted.